2004
DOI: 10.1073/pnas.0407992101
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome of severe acute respiratory syndrome analyzed by two-dimensional gel electrophoresis and mass spectrometry

Abstract: We have investigated the plasma proteome by using 2D gel electrophoresis and MS from patients with severe acute respiratory syndrome (SARS). A complete proteomic analysis was performed on four patients with SARS in different time courses, and a total of 38 differential spots were selected for protein identification. Most of the proteins identified are acute phase proteins, and their presence represents the consequence of serial cascades initiated by SARS-coronavirus infection. There are several proteins that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 54 publications
5
85
0
2
Order By: Relevance
“…In addition, Prx II, a known cytoplasmic form, has also been found in the plasma of multiple sclerosis patients with severe acute respiratory syndrome; T cells may be a source of secreted Prx II in plasma. 146 Another study also found Prx II in plasma and demonstrated it to be an interaction partner of Trx1. 147 Mouse Prx IV, which contains a signal peptide similar to that of human Prx IV, is apparently not secreted and appears to be a cytoplasmic signaling protein, 148 whereas rat Prx IV appears to function as a secreted protein.…”
Section: Peroxiredoxins (Prx)mentioning
confidence: 96%
“…In addition, Prx II, a known cytoplasmic form, has also been found in the plasma of multiple sclerosis patients with severe acute respiratory syndrome; T cells may be a source of secreted Prx II in plasma. 146 Another study also found Prx II in plasma and demonstrated it to be an interaction partner of Trx1. 147 Mouse Prx IV, which contains a signal peptide similar to that of human Prx IV, is apparently not secreted and appears to be a cytoplasmic signaling protein, 148 whereas rat Prx IV appears to function as a secreted protein.…”
Section: Peroxiredoxins (Prx)mentioning
confidence: 96%
“…A 2D-PAGE approach was recently applied to compare plasma samples obtained from patients with severe acute respiratory syndrome (SARS) and healthy individuals (25). Twenty-two plasma samples from four different SARS patients were separated by 2D-PAGE using a narrow-range IPG strip (pH 4 -7), and the resulting profiles were compared with those obtained from six healthy plasma samples.…”
Section: Quantitative Comparison Of Biofluidsmentioning
confidence: 99%
“…By the same technique, truncated forms of a1-antitrypsin were discovered in serum samples of patients presenting with severe acute respiratory syndrome [77]. Chen et al [78] studied four patients with severe acute respiratory syndrome. After 2-DE, a total of 38 differential spots were selected for protein identification, and most of them corresponded to acute phase proteins.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%